Developing a sustainable, post treated, half warm mix asphalt for structural surface layer. (1st August 2022) - Amoori Kadhim, Mustafa; Al-Busaltan, Shakir; Dulaimi, Anmar; Sadique, Monower; Al Nageim, Hassan; Al-Kafaji, Muna; Al-Yasari, Rand
Highlights: A new sustainable half warm emulsified bituminous mixture has been developed. The moisture sensitivity improved by incorporating waste glass. Rutting resistance for the half warm mixtures was lower than for the cold mixture. Post treatment using microwave energy was an effective technique to produce half warm emulsified bituminous mixture. Abstract: Sustainability and materials recycling have increasingly acquired importance in various aspects of life. It has well known that 95% of roads are paved with hot mix asphalt (HMA), their raw materials require a lot of energy to prepare and lead to the release of a considerable amount of CO2 into the environment. As a result, developing new technologies to prepare a new sustainable asphaltic mixture that consumes less energy and is eco-friendly becomes a necessity. This research aims to develop a sustainable half-warm asphalt mix by exposing the cold bituminous emulsion mixture (CBEM) to a post treatment using microwave energy technique, as well as utilising crushed glass waste as fine aggregate. The newly developed mix (half warm bituminous emulsion mixture, or HWBEM) is evaluated in terms of two main failure distress (cracking and rutting) using wheel track (WTT) and indirect tensile tolerance index, or cracking tolerance index (CT-index), in addition to the volumetric and durability evaluation in term of air voids content (AV) and retained Marshall stability test (RMS). Tests results regarding mechanical, volumetric, and durability properties indicated that the developed mixture was relatively comparable in some of the properties with referenced CBEM and superior in one aspect. Moreover, the sustainability aspect was achieved successfully by replacing a significant amount of virgin fine aggregate with the crushed waste glass. Based on the results of the test program, it can be said that the newly developed HWBEM incorporated waste glass can work as a structural surface layer.